Primes and Consequences: A Systematic Review of Meritocracy in Intergroup Relations - Madeira, Ana Filipa; Costa-Lopes, Rui; Dovidio, John F.; Freitas, Gonçalo; Mascarenhas, Mafalda F. (Frontiers in Psychology, 2019)
Psychological interest in Meritocracy as an important social norm regulating most of the western democratic societies has significantly increased over the years. However, the way Meritocracy has been conceptualized and operationalized in experimental studies has advanced in significant ways. As a result, a variety of paradigms arose to understand the social consequences of Meritocracy for intergroup relations; in particular, to understand the adverse consequences of Meritocracy for disadvantaged group members. The present research seeks to understand whether there is strong support for the idea that (manipulated) Meritocracy disproportionally affects members of low status groups, and also to understand which specific components of this norm have been successfully manipulated and to what consequences. And this is particularly important given the recent call for greater transparency in how the success of experimental manipulations is reported. Thus, we carried out a systematic review examining the content of different prime tasks, summarizing prime manipulation checks’ effectiveness, and analyzing whether priming Meritocracy leads to less favorable orientations toward low status groups. Results across 33 studies revealed that despite the existing differences in the components highlighted, the salience of any of the Meritocracy dimensions facilitates the use of internal causal attributions, negative evaluations and stereotyping towards low status groups, affecting negatively decisions involving low-status group members, particularly in specific domains, as organizational contexts. These results carry both practical and theoretical implications for future research on the role of Meritocracy in intergroup settings.